Assessment and Analysis of the Restriction of Retroviral Infection by the Murine APOBEC3 Protein - Aydin, Halil Ibrahim (Université d'Ottawa / University of Ottawa, 2011)
Human APOBEC3 proteins are host-encoded intrinsic restriction factors that can prevent the replication of a broad range of human and animal retroviruses such as HIV, SIV, FIV, MLVs and XMRV. The main pathway of the restriction is believed to occur as a result of the cytidine deaminase activity of these proteins that converts cytidines into uridines in single-stranded DNA retroviral replication intermediates. Uridines in these DNA intermediates disrupt the viral replication cycle and also alter retrovirus infectivity because of the C-to-T transition mutations generated as a result of the deaminase activity on the minus strand DNA. In addition, human APOBEC3 proteins also exhibit a deamination-independent pathway to restrict retroviruses that is not currently well understood. Although the restriction of retroviruses by human APOBEC3 proteins has been intensely studied in vitro, our understanding of how the murine APOBEC3 (mA3) protein restricts retroviruses and/or prevents zoonotic infections in vivo is very limited. In contrast to humans and primates that have 7 APOBEC3 genes, mice have but a single copy. My study of the function and structure of mA3 revealed that it has an inverted functional organization for cytidine deamination in comparison to the human A3G catalytic sites. I have also found that disruption of the integrity of either of these catalytic sites substantially impedes restriction of HIV and MLV. Interestingly, our data shows that mA3 induces a significant decrease in retroviral activity of HIV and MLVs by exploiting both deamination-dependent and -independent pathways. However, the deaminase activity of mA3 is essential to confer long-term restriction of retroviral infection. My observations suggest that mA3 has dual activities, both deamination-dependent and -independent, that work cooperatively to restrict a broad range of human and animal retroviral pathogens. In the context of the intrinsic immune system, APOBEC3 proteins provide a powerful block to the transmission of retroviral pathogens that very few have found ways to evade.
Keywords: Retrovirus; MLV; APOBEC3; Gammaretrovirus; Innate Immunity; Intrinsic Immunity; Deamination